Von der Nützlichkeit des Unnützen - Samide, Irena (Vestnik za tuje jezike, 2024)
German teachers can enrich their teaching or plan their lessons based on the content, vocabulary, and grammatical structures that appear in German songs. In the six examined textbook series, there are relatively few songs. They appear as introductions to individual lessons or are located on separate pages at the end of the textbook. Most songs are not authentic and have been written specifically for the needs of the respective target audience of foreign language teaching, making it easier for textbook authors to integrate such songs into the concept of the textbook or adapt them to the curriculum. The song lyrics are transcribed and available to learners when solving tasks related to the songs. The most common aspect evaluated is the learners’ listening (and reading) compre-hension. There are an average of three tasks per song, but few of them are introductory or transfer tasks that pursue the higher learning objectives of Bloom’s taxonomy. Learners are mostly asked to recognize information, and only rarely to produce spoken and written texts or to express an opinion. Tasks only occasionally address current social and cultural issues in the German-speaking area. The social forms are not predetermined in the instructions, and learning strategies are only indirectly conveyed through the tasks. Any extensions of the treatment of songs in terms of project work are left to the teachers. Based on the summarized results of the quantitative analysis of song treatments with accompanying didactic comments, they key approaches to the treatment of songs in German lessons at Slovenian high schools and grammar schools are identified and presented.
Keywords: didactics of literature; German literature; Jan Wagner; literarna didaktika; literature in foreign language classroom; nemška književnost; poetry; poezija; pouk književnosti